Upaya Penanganan Morning Sickness Pada Ibu Hamil Trimester Pertama Di Puskesmas Grogol - HAPSARI, DISTYANA NUNUNG; , WINARSIH NUR AMBARWATI (2016)
Background : Pregnancy is the fertilization or conception is meeting between ovum and sperm occurs in ampulla in the fallopian tubes . After ovulation ends infundibulum shaped protrusions like fingers and coated cilia sweep the ovum will catch and get into the fallopian tube and into the ampulabecause peristaltic contractions and movements silia and ovum can only survive for 24 hours after ovulation . Based on the results of the report Lacase of 367 pregnant women experience nausea and vomiting that occur in the first trimester. Objective : to deal with morning sickness in the first trimester pregnant women in accordance with the standards of nursing care. Methods : The method used is descriptive in Ny. C with a case study approach , namely by do nursing care at the start of the assessment , intervention , implementation and evaluation. Result : After 3 days of nursing care during home visits diagnosis that appears on Ny . C is the lack of knowledge related to the lack of information (handling morning sickness ). Conclusion : The problem that occurs on the client nursing partially resolved so that interventions should still be continued.